EVALUATION OF RISK FACTORS AND PREVALENCE OF DEPRESSIVE DISORDERS AMONG RURAL FEMALES IN DISTRICT FAISALABSD - Z. Batool; S. R. S. Abbasi; M. I. Zafar; S. Hameed (Journal of Animal and Plant Sciences, 2008)
We all go through ups and downs in our mood. Sadness is a normal reaction to life’s struggles, setbacks, and disappointments. We may feel “down in the dumps” for a short period of time, but gradually the painful feelings dissipate and we move on with our lives—often the wiser for the experience. But if these feelings of sadness don't go away or if they are so intense that they interfere with your ability to work, study, eat, sleep, and enjoy life, you may be suffering from depression. We are all at risk for developing a depressive illness. People of all ages, races, and social class can become depressed. No one is completely immune to this condition. Everyone experiences feelings of unhappiness and sadness occasionally. But when these depressed feelings start to dominate everyday life and cause physical and mental deterioration, they become what are known as depressive disorders. Nearly twice as many women as men develop depression and related disorders at some point in their lives. A woman's unique biological, psychosocial and cultural factors may increase her risk of depression. Married women are more depressed. It is usually because a married woman has many responsibilities to fulfill. The present study was conducted in district Faisalabad.The purpose was to study the risk factors, prevalence and impact of depression on married women. Women were interviewed through a well-structured interviewing schedule consisting of close-ended questions. The sample size was 200 respondents. Four villages from two union councils of one rural town were selected randomly through multi stage sampling technique. This study entails with the perception of rural married women about the risk factors, prevalence and impact of depressive disorder. After a comprehensive research the factors that cause depression in married women are husband wife conflict, in-laws conflict, baradari conflict, death of a close relative, loss of children, loss of husband’s job, financial difficulties, addiction in family, long term of stress at home, rented house, pregnancy, miscarriage, infertility, early motherhood, caring of children and aging parents, single parenthood and workload due to large family. On the basis of results and findings of the study, different recommendations are proposed, focusing on preventive measures for depression and emphasizing on improving the mental health of women. The study has deeply indicate that low socio-economic status, conflict with husband and in-laws, early motherhood and heavy workload are the major risk factors of depression among women
Keywords: Women perceptions; risk factors; depressive disorders